2016
DOI: 10.1371/journal.ppat.1006102
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Screen Identifies Human Interferon-Stimulated Regulators of Listeria monocytogenes Infection

Abstract: The type I interferon (IFN) activated transcriptional response is a critical antiviral defense mechanism, yet its role in bacterial pathogenesis remains less well characterized. Using an intracellular pathogen Listeria monocytogenes (Lm) as a model bacterial pathogen, we sought to identify the roles of individual interferon-stimulated genes (ISGs) in context of bacterial infection. Previously, IFN has been implicated in both restricting and promoting Lm growth and immune stimulatory functions in vivo. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 78 publications
2
33
0
Order By: Relevance
“…Several ISGs have been identified as having antibacterial effects, including MYD88 and TRIM1. 36 Furthermore, IFNs can induce a more systemic defense by activating NK and CD8+ T cell cytotoxicity as well as by increasing antigen presentation and recruitment of the adaptive immune system.…”
Section: Type I Ifns and Their Antipathogen Effectsmentioning
confidence: 99%
“…Several ISGs have been identified as having antibacterial effects, including MYD88 and TRIM1. 36 Furthermore, IFNs can induce a more systemic defense by activating NK and CD8+ T cell cytotoxicity as well as by increasing antigen presentation and recruitment of the adaptive immune system.…”
Section: Type I Ifns and Their Antipathogen Effectsmentioning
confidence: 99%
“…Our previous studies demonstrated that FcγRIa did not promote cellular uptake of intracellular bacteria S. flexneri or S. Typhimurium. Additionally, FcγRIa did not confer an invasive phenotype to L. innocua, a non-pathogenic Listeria species closely related to Lm (8). These findings suggest that a bacterial Fcγ receptor ligand is specific to pathogenic Listeria and potentially provides an advantage in survival and dissemination during infection.…”
Section: Fcγria-mediated Internalization Is Specific To Pathogenic LImentioning
confidence: 83%
“…Strikingly, we previously found that Lm is internalized by FcγRIa-expressing cells independently of antibody interaction or ITAM-mediated signaling, hallmarks of IgG-opsonized particles uptake. Additionally, this process did not involve wellcharacterized host Lm internalization receptors (E-cadherin and c-Met) or bacterial surface internalins (InlA and InlB) (8). Thus, FcγRIa-mediated Lm entry occurs through a non-canonical mechanism.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations